Da província à corte: deputados paraibanos e a formação do estado nacional (1831-1840) - Santos, Jerlyane Dayse Monteiro dos (2014)
This dissertation - belonging to the line of research of Regional History in the Post Graduate Program in History of the Federal University of Paraíba, within the area of Historic Culture - comes on the relationship between Paraiba and the formation of the national state during the Regency period (1831- 1840) from the look of political culture . The Regency is the period between the abdication of Emperor d. Pedro I and the adult age of your child d. Pedro II. Aware of the importance of this period for the formation of the national state analyzed by the Annals of the Brazilian Parliament and the provincial government documents, how was the participation of Paraíba deputies in the Chamber of Deputies, we seek to understand their contribution to the debates that traced the course of formation of the nationstate . After the abdication, April 7, 1831, passed the House Representative to discuss important issues for maintaining national unity. Between the first measure taken by the institution include the creation of the National Guard in 1832 as a way to contain the expressions of people and troops who invaded the streets of the Court and have spread to other provinces. In 1834 , after numerous discussions among parliamentarians, about the importance of giving the provinces federal autonomy , the Additional Act was approved. The Additional Act added articles of Law of the Imperial Constitution, something unheard for the new Empire. And among other things, established the creation of a Legislative Assembly in each province. This new formal institution of power allowed the provinces they held some autonomy, while slowly withdrew from councils the power that was characteristic of them since the colonial period. During this period were put into political debate projects liberal and conservative character, and perceive through the Annals of the Brazilian Parliament the involvement of parliamentarians paraibanos in debates that were on the order of the day, at the same time, the defense of their positions was not fixed, but mutable. Changed their position according to the interests of the political group, or even their personal interests. Thus, we analyzed the provincial political scene as well as we seek to demonstrate the relationship between deputies paraibanos and their allied bases in the province, what we understand to be the local political elite.